Bacillus atrophaeus: main characteristics and biotechnological applications – a review. (20th June 2014) - Sella, Sandra R. B. R.; Vandenberghe, Luciana P. S.; Soccol, Carlos Ricardo
Abstract: The genus Bacillus includes a great diversity of industrially important strains, including Bacillus atrophaeus (formerly Bacillus subtilis var. niger ). This spore-forming bacterium has been established as industrial bacteria in the production of biological indicators for sterilization, in studies of biodefense and astrobiology methods as well as disinfection agents, in treatment evaluation and as potential adjuvants or vehicles for vaccines, among other applications. This review covers an overview of the fundamental aspects of the B. atrophaeus that have been studied to date. Although the emphasis is placed on recent findings, basic information's such as multicellularity and growth characteristics, spore structure and lifecycle are described. The wide biotechnological application of B. atrophaeus spores, including vegetative cells, is briefly demonstrated, highlighting their use as a biological indicator of sterilization or disinfection.